CDIO initiative in basic sciences courses in Diploma Chemical Engineering / Sarifah Fauziah Syed Draman, Noraini Razali - Syed Draman, Sarifah Fauziah; Razali, Noraini (UiTM Press, 2020)
This paper shares the experience of the Diploma in ChemicalEngi neering (EH110) of UiTM Bukit Besi Campus in using basic science cources to achieve the CDIO (Conceive - Design -Implement - Operate) goal of value-added engineering systems. In particular, it focuses on the Semester 1 course CHE 142 (Inorganic and Physical Chemistry) and semester 2 course CHE 143 (Organic and Analytical Chemistry). This course offers students understandings of concepts in chemistry while retaining the exciting aspects of chemistry so as to develop interest in the study of chemistry as a discipline. Topics covered are atomic stuructures, chemical bonding, acids and bases, redox reaction, chemical thermodynamics, chemical equilibrium and chemical kinetics. Meanwhie, in CHE 143 course, students learn to recognize and name organic functional groups. Students learn about systems to represent organic molecules, how structure affects physical properties, drawing resonance forms with proper arrow convention, organic acid-base reactions, substitution and elimination reactions and organic syntheses.